A Novel and Efficient Approach to Retrieve Data from Cloud - Lathar, Pankaj; Singh, Yudhvir; Sharma, Girish Kumar (International Journal of Computer Sciences and Engineering, 2014)
String matching is a very important subject in the wider domain of text processing. String matching algorithms are basic components used in implementations of practical softwares existing under most operating systems. Moreover, they emphasize on programming methods that serve as paradigms in other fields of computer science. In Text processing systems users search a pattern of string from a given text. String matching is fundamental to database and text processing applications. Every text editor contains a mechanism to search the current document for arbitrary strings. This paper aims at describing a new string matching algorithm for various applications. A new algorithm has been designed which is based on a 2D structure.